Gender and Family Issues in the Workplace - Ehrenberg, Ronald G.; Blau, Francine D. (Book collections on Project MUSE., 1997)
Claudia Goldin presents evidence that female college graduates are rarely able to balance motherhood with "career track" employment, and Jane Waldfogel demonstrates that having children results in substantially lower wages for women. Do parental leave policies improve the situation for women? Gender and Family Issues in the Workplace offers a variety of perspectives on this important question. Some propose that extended leave improves women's wages by allowing them to preserve their job tenure. Other economists express concern that federal leave policies prevent firms and their workers from acting on their own particular needs and constraints, while others argue that because such policies improve the well-being of children they are necessary to society as a whole. Olivia Mitchell finds that although the availability of unpaid parental leave has sharply increased, only a tiny percentage of workers have access to paid leave or child care assistance. Others caution that the current design of "family-friendly policies" may promote gender inequality by reinforcing the traditional division of labor within families. The various points of view combine to form an innovative and up-to-date investigation into women's chances for success and equality in the modern economy.